Management of extensive injury in the upper third face: clinical case report - Lyra, Carolina Viana Vasco (2021)
Facial soft tissue injuries can be considered a study challenge for professions that work with aesthetic and functional rehabilitation in this area, such as maxillofacial surgeons. These injuries can play a prominent role in the care of traumatized patients due to their potential to compromise the individual's life, as, when badly handled, they leave sequelae that present emotional and functional repercussions and possible permanent deformities. male patient, 33 years old, treated at the Hospital da Restauração Governador Paulo Guerra, Recife, Pernambuco, with a history of falling an iron gate on his head (work accident), attending a mild traumatic brain injury and extensive wound in the face and scalp. The established treatment was antisepsis with 2% chlorhexidine gluconate in the region, copious irrigation with 0.9% sterile saline and suturing in planes. Soft tissue lesions on the face have the potential to compromise the individual's life and may cause sequelae that have emotional and functional repercussions and possible permanent deformities. The diagnosis and proper management by the maxillofacial surgery and traumatology team is of paramount importance.